Los desafíos éticos del post-estructuralismo: Encuentros con el psicoanálisis a través de la teoría del trauma - Pérez Baquero, Rafael (Bollettino Filosofico, 2021)
This paper aims at delving further into the entanglements between psychoanalytical and poststructuralist assumptions underlying contemporary theories on trauma. Scholars such as Cathy Caruth, Geoffrey Hartman, and Shoshana Felman have elaborated a groundbreaking theory of how to depict overwhelming historical experiences, by means of the notion of trauma. With a view to bringing new light into their ideas, this paper aims at understanding them as responses to the ethical flaws stemming from the poststructuralist perspectives these authors endorses. In order to address this challenge, this article highlights the role that Derrida’s, Paul de Man’s and Levinas’ legacies play within contemporary theories on trauma. Keywords: Ethics, Deconstruction, Post-structuralism, Psychoanalysis, Trauma